Lifelines for Money Misfortunes - Levine Mark (John Wiley & Sons, 2008)
An encouraging guide to planning for life's unexpected surprises For the past three decades, Stephen Pollan has introduced thousands of individuals to innovative new strategies for dealing with their careers, money, and numerous other complexities of the "business of life." Through his bestselling books-as well as television appearances and counseling services-he has empowered people to take charge of their lives. Now, with Lifelines for Money Misfortunes, Pollan looks to share more of his cutting-edge ideas with a wide range of readers, regardless of their income level or comfort with handling money. Lifelines for Money Misfortunes takes a holistic approach to dealing with the unpredictable accidents, disasters, and crises that disrupt our carefully planned lives. Drawing on Pollan's expert legal and financial experience as well as the experiences of numerous savvy professionals-including mediators, career counselors, social workers, insurance adjustors, and more-this book reveals both the secrets of personal crisis management and the tactics for overcoming the most common and worrying disasters readers might face. It also outlines coping plans that can be used to handle financial and other matters during any crisis, and illustrates the most effective ways to implement them. Filled with real-world stories of individuals who have gone through the disasters discussed-including illness, job loss, and the death of a spouse-Lifelines for Money Misfortunes offers a plan for personal crisis management that can be used by anyone, no matter what type of catastrophic events they may be facing. No one is better qualified to help readers at their most vulnerable than Stephen Pollan, and with Lifelines for Money Misfortunes, they'll quickly discover why